2000
DOI: 10.1152/ajprenal.2000.278.1.f75
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal water metabolism in mice lacking the type 1A receptor for ANG II

Abstract: Mice lacking AT(1A) receptors for ANG II have a defect in urinary concentration manifested by an inability to increase urinary osmolality to levels seen in controls after thirsting. This defect results in extreme serum hypertonicity during water deprivation. In the basal state, plasma vasopressin levels are similar in wild-type controls and Agtr1a -/- mice. Plasma vasopressin levels increase normally in the AT(1A) receptor-deficient mice after 24 h of water deprivation, suggesting that the defect in urine conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
100
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(109 citation statements)
references
References 34 publications
6
100
3
Order By: Relevance
“…42 Complete deletion of the AT 1a receptor resulted in an animal with enhanced osmotic and sympathetic responses, as well as altered renal function. 18,19,44 However, there are limits to the use of these genetic models. First, because AT 1 receptors are widely expressed in brain and periphery, it is difficult to determine the regional functionality in models in which the receptor is globally deficient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…42 Complete deletion of the AT 1a receptor resulted in an animal with enhanced osmotic and sympathetic responses, as well as altered renal function. 18,19,44 However, there are limits to the use of these genetic models. First, because AT 1 receptors are widely expressed in brain and periphery, it is difficult to determine the regional functionality in models in which the receptor is globally deficient.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies in mice lacking AT 1a receptors show that water intake is also increased, similar to that seen in mice exposed to Ad-AT 1a -shRNA. 44 This may be related to changes in renal function or to changes in the brain reninangiotensin system. 44 Davisson et al 17 showed that brain AT 1b receptors are important in the mediation of the Ang IIinduced drinking responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urine of male and female mPges1 ϩ/ϩ and mPges1 Ϫ/Ϫ mice was collected by bladder massage before and after a 12-h period of water deprivation. Urine osmolalities were then immediately measured using a vapor pressure osmometer (Wescor Instruments, Logan, UT) as described previously (25).…”
Section: Assessment Of Urinary Concentrating Capacitymentioning
confidence: 99%
“…Ang AT1a receptors are critical in the control of blood pressure, autonomic function, and fluid/electrolyte balance, as seen in studies of AT1a gene deletion models. 9,10 Ang AT2 receptors are more prevalent during development and are thought to mediate vasodilation and cell growth. 11,12 There is also evidence for interaction with ACE expression, with suggestions that AT2 activation decreases ACE activity.…”
mentioning
confidence: 99%